2010
DOI: 10.1002/prot.22836
|View full text |Cite
|
Sign up to set email alerts
|

Combined use of computational chemistry, NMR screening, and X‐ray crystallography for identification and characterization of fluorophilic protein environments

Abstract: (19)F NMR screening of fluorinated fragments with different Local Environment of Fluorine, a.k.a. LEF library, is an experimental methodology which, beyond providing useful starting fragments for fragment-based drug discovery projects, offers, in combination with crystal and computational analysis, an approach for the identification of fluorophilic hot-spots in the proteins of interest. The application of this approach in the identification of fluorinated fragments binding to the serine protease trypsin, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 47 publications
1
41
0
Order By: Relevance
“…Similar interactions of fluorine atom with carbonyl oxygen of various amino acids have been previously observed in various protein structures with a frequency of over 9%. [31] Since Gly48 is located in the flap, for inhibitor 3 , these F….OC interactions with Gly48 may tend to stabilize the flexible flap region as well as improve the binding affinity for HIV-1 protease complex. The structure also shows hydrogen bonding interactions of urethane NH with the backbone carbonyl oxygen of Gly27.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar interactions of fluorine atom with carbonyl oxygen of various amino acids have been previously observed in various protein structures with a frequency of over 9%. [31] Since Gly48 is located in the flap, for inhibitor 3 , these F….OC interactions with Gly48 may tend to stabilize the flexible flap region as well as improve the binding affinity for HIV-1 protease complex. The structure also shows hydrogen bonding interactions of urethane NH with the backbone carbonyl oxygen of Gly27.…”
Section: Resultsmentioning
confidence: 99%
“…We also presume that our structure-based fluorine substitution may improve molecular binding properties in the HIV-1 protease active site through noncovalent interactions involving fluorine. [17,18] This may result in potent antiviral activity against multi-drug resistant HIV-1 variants. Herein, we report an enantioselective synthesis of gem -difluoro- bis -THF ligands and their conversion to gem -difluoro- bis -THF containing HIV-1 protease inhibitors resembling darunavir.…”
Section: Introductionmentioning
confidence: 99%
“…All protein heteroatoms that are at a distance of 3.2 from the ligand fluorine atoms were selected using the previously described procedure. [15] This value is slightly larger than the sum of the van der Waals radii, to allow for uncertainty in measurements. The analysis was performed for all structures available in the PDB as of August 2009.…”
Section: Methodsmentioning
confidence: 99%
“…This LEF (Local Environment of Fluorine) library [14] has since been successfully used in 19 F NMR screening of different targets. [15] The aim of the current analysis is to demonstrate a correlation between the fluorine isotropic chemical shift measured in 19 F NMR spectra and the type of fluorine-protein interactions observed in crystal structures. It is envisaged that these findings will aid in the rational drug design process by providing guidance in the selection of fluorinated moieties to be judiciously incorporated into molecules in order to create favorable interactions with the receptor.…”
Section: Introductionmentioning
confidence: 98%
“…1316 Vulpetti et al identified fluorinated fragments binding to trypsin by 19 F NMR screening and crystal structure determination and described a general approach to identify fluorophilic hot-spots in proteins using crystal and computational analysis. 17 Recently, Pollock et al investigated the impact of fluorine–protein interactions on the binding affinity of a menin–MLL inhibitor and introduced their computational algorithm FMAP, which aims to facilitate the rational design of fluorine–protein interactions. 18 …”
mentioning
confidence: 99%